Prevalence and molecular characterization of drug-resistant Mycobacterium tuberculosis in Heyuan City in China - Qiu, Dan; Ma, JianHong; Liu, ZhiFang; Zeng, XiangXing (Frontiers in Cellular and Infection Microbiology, 2025)
PurposeTuberculosis (TB) represents a significant global public health challenge, with China identified as a high-burden country. Data on the prevalence of drug resistance is crucial for informing the selection of appropriate pharmacological interventions for the treatment of drug-resistant tuberculosis (DR-TB).To evaluate the prevalence and drug resistance patterns among patients with DR-TB in Heyuan City, China.MethodsAll 291 patients registered between April 2021 and March 2023 were tested for drug resistance, and information about their medical history and demographics was collected directly from the hospital’s computer database. Eight genes were analyzed for mutations associated with resistance to five antituberculosis drugs: the katG, ahpC, and inhA promoters for isoniazid (INH); rpoB for rifampicin (RIF); embB for ethambutol (EMB); gyrA for fluoroquinolones (FQs); and rrs and rpsL for streptomycin (STR). All strains were genotyped using fluorescence melting curve analysis.ResultsIn Heyuan, 24.4% (71/291) of patients with treatment-resistant TB were resistant to at least one drug. Following are the rates of general resistance to each drug: RIF (28/272, 10.29%), INH (38/274, 13.87%), FQs (10/259, 3.86%), EMB (20/248, 8.06%), and STR (15/150, 10.00%). Age or gender had no statistically significant impact on the likelihood of developing drug resistance. Nevertheless, a statistically significant difference was observed between the three strategies of drug resistance testing, AFB testing, and MTB antibody testing. There were 48 cases of single-drug resistance and 23 cases of multiple-drug resistance among the 71 drug-resistant patients. Eight genes had 127 altered nucleotide sequences, with KatG315 (20.47%) having the most significant incidence of mutations. The top three mutated genes were rpoB (32.28%), katG (23.62%), and embB (15.75%).ConclusionThese findings may be helpful in Heyuan City for the quick molecular identification of DR-TB isolates in clinical samples.